Cooperativas agropecuárias no Norte do Paraná : as trajetórias da VALCOOP e COROL - Marandola, Maria Eduvirge (2000)
Discusses the transformations occurred in the cattle raising and agricultural cooperatives in Paraná state, in the period from 1970 to 1998, through case study that traces the trajectory of two cattle raising and agricultural cooperatives located in the north area of the State of Paraná. These cooperatives had origin in the coffee plantation economy and, in the decade of 70's, they became cereal receivers cooperatives. One stayed as cereal trader and the other, besides the commercial activities, it possesses also agro-industrial activities. Through the grouping of accounting information the capitalization and the growth of two were demonstrated. The found results revealed that those cooperatives had two moments. The first, from 1970 to approximately 1982, marked by deep internal transformations: growth of the immobilized what turned them structurally larger, growth of the own capital and positive operational results. The second moment extended from 1983 to 1998 and it demonstrated inexpressive growth in the immobilized, exhaustion in the capacity to generate surpluses and difficulty of self-sustaining. The first moment is characterized by abundant government resources for the deployment of the technological modernization in the agriculture. In the second moment, it occurred the shrinking of credit, the approval of the auto-managing and the opening of the economy. The declining results of both cooperatives, in the period 83 to 98, demonstrates that, very auspiciously those cooperatives had undertaken internal strategies to make possible self-sustaining, they were unable to maintain satisfactory results, in the absence of institutional politics.